G264(P) Menb (bexsero) immunisation side effects in extremely premature infants (<28 weeks). (12th March 2018) - Mukherjee, D; Mukherjee, A; Rajai, A; Senthil, S; Osagie, NE
Abstract : Background: The UK on 01 September 2015 became the first country to introduce Meningococcal B (Bexsero) vaccine into the national infant immunisation programme. Bexsero is recommended for all infants as part of their routine vaccinations at ages 2, 4 and 12 months alongside other regular vaccines. Bexsero is highly immunogenic and is estimated to protect against 73%–88% of MenB strains causing invasive meningeal disease (IMD) in England and Wales1. Objective: We retrospectively evaluated tolerability of Bexsero vaccine on preterm babies in our neonatal intensive care unit. Methods: Retrospective observational study comparing tolerability of the vaccines in the two time periods, before (Period 1, n=13) and following (Period 2, n=13) the introduction of the new vaccine (Bexsero) in September 2015. We inspected the clinical status 48 hours prior to and 48 hours post immunisation to evaluate vaccine tolerance during these two time periods. Results: Before introduction of Men B vaccine, there was convincingly low levels of side effects in our babies following routine immunisation. After introduction of MenB vaccine, 46% (6/13) of babies became unwell within 24–48 hours of immunisation; 30% (4/13) needed escalation in respiratory support. 15% (2/13) needed rescue ventilation after Bexsero vaccination. Conclusions: We hypothesised that all babies immunised with Bexsero alongside regular vaccines will remain clinically stable and will tolerate the vaccines without any appreciable side effects. 46% of our babies became unwell following the combined MenB programme, raising speculations about safety profile of the Bexsero in preterm infants. Precautionary monitoring following vaccination is recommended. Larger studies are needed to ensure safety of Bexsero vaccine in preterm babies.